Implementation of Discovery Learning Model Towards Students Learning Outcome of XI-IPA1 Students on the Respiratory System Materials at Pangsid High School - Akmal Akmal; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2019)
This Classroom Action Research (CAR) aims to determine the effect of the implementation of Discovery Learning models towards learning outcome of XI-IPA1 students, on the respiratory system subject matter at SMA 1 Pangsid. This study was conducted in two cycles, each cycle consist of four phases: planning, action, observation and reflection. The subjects were XI IPA 1 students school year 2015/2016, which is amounted to 32 people, consisting of 10 male students and 22 female students. Data analysis was performed with a descriptive quantitative technique. The results showed an increase in student learning outcomes in the respiratory system materials. Improving student learning outcomes from a base score for cycle 1 and cycle II is also changing. Average activity of in the first cycle is equal to 22,68%, then increased to 77,32% in the second cycle. Classical learning 93,%8 achievement has exceeded 85% in the second cycle. This condition shows the results of student learning has high category.